(3GdeRjL GdJShjbj GdeUQaj h CKQg aj GdUhQI GdeOQcI ddRHGFf (B/s - (3WGdH, YdGA aQMGfs; (3GdYWGQ, aDGOj MehOjs; (3TjGY, MSGe MSjf s ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3eaghe JShjb GdNOeGJ GdeUQajI h CgejJg , GdeRjL GdJShjbj GdeUQaj , GdUhQI GdeOQcI dOi GdRHGFf , hUa h JTNjU eJZjQGJ GdeRjL GdJShjbj GdeUQaj h eJZjQGJ GdUhQI GdeOQcI , GNJHGQ aQVjGJ GdJHGjf ddeUGQa aj JHfj eJZjQGJ GdOQGSI , GNJHGQ aQVjGJ GdGQJHGW h aQVjGJ GdGJLGg Hjf eJZjQGJ GdOQGSI , GdGSJfJGLGJ h GdJhUjGJ(B.s
(3eQGLY U(B.247 (3;edGMb U(B.237s
Keywords: (3COGQI GdeHjYGJs; (3GdHfhcs; (3GdJShjbs; (3GdNOeGJ GdeUQajIs